New developments in the treatment of diabetic macular edema: latest clinical evidence. (January 2012) - Golan, Shani; Lowenstein, Anat
Diabetic retinopathy is a major cause of blindness in the western world and its incidence is expected to increase with the incidence of the diabetes. Macular edema is a major cause of visual impairment in the diabetic population. Laser therapy and tighter control of metabolic factors are the cornerstone of treatment. However, it recently became evident that other treatments, particularly pharmacological ones, can provide good results and should be considered for these patients. Medical therapies consist of two major classes of agents: anti-inflammatory drugs, such as intravitreal corticosteroids, some of which are delivered by means of extended-release technologies, and anti-VEGF agents. Agents targeting TNF-α and PKC-ββ2 are also implicated in the pathogenesis of diabetic retinopathy and are currently under investigation. Surgical therapies are usually implicated in the treatment of diabetic macular edema that is resistant to other treatment strategies, especially in cases that have specific anatomic characteristics. Surgical options include pars plana vitrectomy with or without internal limiting membrane peeling, combination therapy of pars plana vitrectomy plus intravitreal steroid or anti-VEGF, or the use of intravitreally administered pharmacological agents such as microplasmin prior to or during vitrectomy. This article reviews the current developments in treatment for diabetic macular edema.